One-pot production of d-allulose from inulin by a novel identified thermostable exoinulinase from Aspergillus piperis and Dorea sp. d-allulose 3-epimerase. (December 2020) - Li, Wen; Zhu, Yingying; Jiang, Xiangling; Zhang, Wenli; Guang, Cuie; Mu, Wanmeng
Graphical abstract: Highlights: An exoinulinase was identified from a novel strain, A. piperis CBS 112811. The enzyme displayed the maximal activity as 3750 U mg −1 at pH 6.0 and 55 °C. The enzyme was stable up to 60 °C for 5 h, showing a relatively high thermostability. One-pot production of d -allulose was developed using exoinulinase and DAEase. The yield of d -allulose reached 21.4 g L −1 with 100 g L −1 inulin as a substrate using the two-enzyme system. Abstract: Inulin has been widely used as a cheap bioresource for producing many valuable products by enzymatic hydrolysis or microbial fermentation, such as high-fructose syrup and fructooligosaccharides. In this work, a one-pot two-enzyme reaction system was developed to produce d -allulose from inulin using A. piperis exoinulinase and Dorea sp. d -Allulose 3-epimerase. The exoinulinase that was identified from Aspergillus piperis CBS 112811 was cloned and intracellularly expressed in Escherichia coli . The enzyme displayed the maximal activity as 3750 U mg −1 at pH 6.0 and 55 °C. For the effects of different cations, Mn 2+ simulated the enzyme activity by 41 %. When 10 g L −1 inulin was hydrolyzed by A. piperis exoinulinase, the conversion rate reached 98 % within 6 h. Furthermore, the optimum pH, temperature and the ratio of the two enzymes loaded for one-pot reaction were measured to be pH 6.0, 60 °C and 15/15 U mL −1, respectively. The conversion rate of inulin to d -allulose reached 23.3 % after reaction for 4 h with 10 g L −1 inulin. When adding 100 g L −1 as a substrate, 21.4 g L −1 d -allulose was produced using the two-enzyme system.